Efficacy of the CryoBalloon Focal Ablation System for the eradication of dysplastic Barrett’s esophagus islands - Künzli, Hannah T.; Schölvinck, Dirk W.; Meijer, Sybren L.; Seldenrijk, Kees A.; Bergman, Jacques G. H. M.; Weusten, Bas L. A. M. (Endoscopy, 2017)
Background and study aim Cryoablation can be used for the treatment of Barrett’s esophagus (BE). A recent dosimetry study, using the CryoBalloon Focal Ablation System (CryoBalloon), demonstrated that 10-second ablations result in complete eradication of BE. However, the efficacy of 10-second ablation in a larger cohort of patients has not been investigated, nor has the potential of precise targeting of specific areas. The aim of the study was to assess the efficacy and performance (i. e. targeting of BE islands) of a 10-second cryoablation using the CryoBalloon.Results A total of 30 patients were enrolled (worst pathology: low grade dysplasia in 14 [47 %], high grade dysplasia in 7 [23 %], early adenocarcinoma in 9 [30 %]). Of the 47 BE islands, 44 (94 %) were adequately targeted. Complete eradication of intestinal metaplasia and dysplasia was observed in 100 % of the completely ablated areas. No stenoses were observed.Conclusion Cryoablation of BE islands using the CryoBalloon is effective. BE islands were effectively targeted.